The Simpsons : Backstage pass - Matt, Groening; Dan, Castellaneta; Julie Kavner; Yeardley Smith; Nancy Cartwright (USA 20th Century Fox Television, 1989)
The Simpsons are very politically incorrect family. Homer works with pride in a nuclear power plant run with more regard for profit that safety. His wife is Marge, a kind of supermom. They have three kids: Bart, an underachiever (""and proud of it""), Lisa (who is as serious and responsible as Bart isn't), and Maggie.
The satiric adventures of a working class family in the misfit city of Springfield.
Language(s): English, French, German Subtitle(s): Danish, Dutch, English, French, German, Italian, Norwegian, Spanish, Swedish
Keywords: Comedy -- Animation -- Tv Series